Light Manipulation in Organic Photovoltaics. Issue 7 (6th July 2016) - Ou, Qing‐Dong; Li, Yan‐Qing; Tang, Jian‐Xin
Abstract : Organic photovoltaics (OPVs) hold great promise for next‐generation photovoltaics in renewable energy because of the potential to realize low‐cost mass production via large‐area roll‐to‐roll printing technologies on flexible substrates. To achieve high‐efficiency OPVs, one key issue is to overcome the insufficient photon absorption in organic photoactive layers, since their low carrier mobility limits the film thickness for minimized charge recombination loss. To solve the inherent trade‐off between photon absorption and charge transport in OPVs, the optical manipulation of light with novel micro/nano‐structures has become an increasingly popular strategy to boost the light harvesting efficiency. In this Review, we make an attempt to capture the recent advances in this area. A survey of light trapping schemes implemented to various functional components and interfaces in OPVs is given and discussed from the viewpoint of plasmonic and photonic resonances, addressing the external antireflection coatings, substrate geometry‐induced trapping, the role of electrode design in optical enhancement, as well as optically modifying charge extraction and photoactive layers. Abstract : Recent advances in light trapping for organic photovoltaics are reviewed in terms of photon management induced by dielectric or metallic micro/nanostructures. Implementing photonic structures into various functional layers or interfaces is highlighted to lead to the redistribution of optical field in the cells and thus the enhanced light harvesting.